Managing Logistic Processes in Activity of Agricultural Enterprises (Economic journal of Lesya Ukrainka Volyn National University, 2017)
Systems of supply, production and marketing of agricultural products, which exist in our days, cannot fully meet market demand. Owners andmanagers of agricultural enterprises are constantly faced with solving complex tasks, such as providing material resources to the enterprise, efficient management of the production process, transportation, warehousing and other operations that are carried out in the process of bringing the finished product to the consumer in accordance with the interests and requirements of the latter, as well as the transfer, storage and processing of relevant information. The tool for solving these problems is logistics, the skillful use of which will ensure the efficient production and delivery of the necessary products to consumerswith a certain level of service.The article deals with the management of logistics processes in the activity of agricultural enterprises. The main types of logistics are highlighted and the logistic processes in them are proceed.
Keywords: Managing Logistic Processes in Activity of Agricultural Enterprises; management, logistics, agricultural enterprise, logistics processes